POLSTRACC: Airborne experiment for studying the polar stratosphere in a changing climate with the High Altitude and Long Range Research Aircraft (HALO) - Oelhaf, Hermann; Pfeilsticker, Klaus (Bulletin of the American Meteorological Society, 2020)
The Polar Stratosphere in a Changing Climate (POLSTRACC) mission employed the German High Altitude and Long Range Research Aircraft (HALO). The payload comprised an innovative combination of remote sensing and in situ instruments. The in situ instruments provided high-resolution observations of cirrus and polar stratospheric clouds (PSCs), a large number of reactive and long-lived trace gases, and temperature at the aircraft level. Information above and underneath the aircraft level was achieved by remote sensing instruments as well as dropsondes. The mission took place from 8 December 2015 to 18 March 2016, covering the extremely cold late December to early February period and the time around the major warming in the beginning of March. In 18 scientific deployments, 156 flight hours were conducted, covering latitudes from 25° to 87°N and maximum altitudes of almost 15 km, and reaching potential temperature levels of up to 410 K. Highlights of results include 1) new aspects of transport and mixing in the Arctic upper troposphere-lower stratosphere (UTLS), 2) detailed analyses of special dynamical features such as tropopause folds, 3) observations of extended PSCs reaching sometimes down to HALO flight levels at 13-14 km, 4) observations of particulate NOy and vertical redistribution of gas-phase NOy in the lowermost stratosphere (LMS), 5) significant chlorine activation and deactivation in the LMS along with halogen source gas observations, and 6) the partitioning and budgets of reactive chlorine and bromine along with a detailed study of the efficiency of ClOx/BrOx ozone loss cycle. Finally, we quantify—based on our results—the ozone loss in the 2015/16 winter and address the question of how extraordinary this Arctic winter was.
Elektronische Reproduktion der Druckausgabe
Gesehen am 20.02.2020